(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Comparative studies have been carried out to estimate the possibilities, purposefulness and efficiency of combine soil tollage, fertilising and sowing machines and units for field crops used on peasant farms under the Baltic conditions. It is found out that most widely used machines and units are aggregates combining pre-sowing tillage of soil (combined cultivators, or revolving power harrow), mineral fertiliser application (pneumatic distributors) and grain sowing (pneumatic, or mechanical sowing machines). As to the agrotechnical terms, the ploughing-sowing aggregates may have limited application. The most suitable are tractor-mounted machines. For combined aggregates preference should be given to more powerful tractors having frontally mounted equipment as well. In contrast to single-operational machines, the use of combined aggregates removes the weather risk, improves the quality of work, raises their efficiency, reduces the consumption of energy and fuel (accordingly, the amount of harmful exhaust gases) and cuts the total costs by 10-18 %. For agrotechnical, energetic, economical and ecological considerations the up-to-date combined aggregates of soil tillage; fertiliser application and sowing are efficient and should be widely introduced on the farms of Latvia.